Wear resistance of Al-12Si alloys by reinforcing TiC and TiN particles - ., Ali Samer, Malek Ali, Projjal Basu, Faiz Ahmad (2013)
This study presents the mechanical properties of the Al-12Si matrix composite reinforced by various amounts of titanium carbide (TiC) and titanium nitride (TiN) particles. The wear behavior was investigated using a pin-on-disk wear testing machine with varying parameters such as normal load, reinforcement percentage, and track velocity. - See more at: http://ascelibrary.org/doi/abs/10.1061/(ASCE)EM.1943-7889.0000743#sthash.nreDdnEI.dpuf